The Role of Employee Human Resources Attribution on Developing Psychological Contract and Turnover Intention in Hong Kong - Kong, Chui Shan (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2020)
The purpose of the study is to illustrate how the human resources (HR) practices affecting the employee outcomes, this study used the concept from social and behavior science with HR management, which were attribution theory and psychological contract, to show how employees perceived the information differently. It further suggested how the process affected the performance of the employees, which illustrated through presenting their turnover intention in this model. In order to test the model, a quantitative survey was designed and conducted through snowball sampling. Multiple linear regression analysis model was used in this study to examine the data sets and tested the hypotheses. The result of this study showed how employees perceived the information could dramatically affect their reaction, as well as employee outcome.Â Furthermore, this study suggested that relational and transactional psychological contract was not a distinct concept, which subverted the past research regarding the types of psychological contract. This study could be used in operation management as the managers should pay attention of how they designed the HR practices could directly affect the employee outcomes and productivity. Limited research focused on the process operating in employees mind and the antecedents of psychological contract leading to certain employee outcomes. This study not only filled up the research gap but also presented the employee attribution and psychological contract concept in a complete manner by linking the variables in the model.Keywords: employee attribution, psychological contract, turnover intention, black box theory